The effectiveness of using class reader programme to enhance students’ perfomance in form three / Muda Ngah - Ngah, Muda (2002)
The aim of this study is to investigate whether the present Class Reader Programme(CRP) is being used effectively or not in the school as inspired by the New Integrated Curriculum of Secondary School (KBSM). Primary and secondary sources are used to elicit the needed information pertaining the topic. Presently one of the five forty minutes English Language periods per week is allocated to CRP. CRP book can be either the simplified version of a literary text or a new story written according to certain language specification. These graded readers classified at different level may, ideally be used with students of different levels of language and reading competency. Last but not least, CRP, therefore is a useful resource for language teaching. It may be used in classroom with a variety of exercises or out of the classroom to encourage students to read intensively on their own.